1989
DOI: 10.1002/jmv.1890280404
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Acute type a hepatitis presenting with hypotension, bradycardia, and sinus arrest

Abstract: The cardiovascular complications of viral hepatitis are not widely recognized. Profound hypotension and a variety of dysrhythmias, including sinus arrest, have been reported in association with viral hepatitis, but most of these cases were described before the advent of specific viral serologic markers. Furthermore, previous instances of cardiovascular complications occurred during the course of an established viral syndrome. We report the cases of two previously healthy women who presented with unexplained hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Hepatitis A leading to pericarditis, myocarditis, and pleural or pericardial effusion has been reported in the literature but is extremely rare (6,7) . Cases of complete heart block following infectious hepatitis have been published (8) and myocarditis following viral infection can lead to complete heart block (9,10) .…”
Section: After Recovery It Provides a Lifelong Immunitymentioning
confidence: 99%
“…Hepatitis A leading to pericarditis, myocarditis, and pleural or pericardial effusion has been reported in the literature but is extremely rare (6,7) . Cases of complete heart block following infectious hepatitis have been published (8) and myocarditis following viral infection can lead to complete heart block (9,10) .…”
Section: After Recovery It Provides a Lifelong Immunitymentioning
confidence: 99%
“…In a recent US report of a case-control study using administration data from Veterans Health Administration, an increased risk of incident AF was found in patients with HCV compared to controls, and the hazard ratio of newly diagnosed AF was 1.42 times higher in patients with HCV [18]. In addition, the presentations of hypotension, bradycardia, and sinus arrest during the acute phase of viral hepatitis have been documented, and may require the implantation of a pacemaker for treatment [19]. Sinus node dysfunction (SND) and atrial arrhythmias were frequently found to associate with each other and thereby coexist, interact, initiate, and perpetuate each other [20].…”
Section: Previous Studiesmentioning
confidence: 99%
“…Cardiac manifestations such as profound hypotension and a variety of dysrhythmias have been rarely reported in adult patients with hepatitis A. 3,4 We describe an adolescent with acute hepatitis A infection who developed bradycardic episodes and a transient hypotension during the course of acute infection.…”
Section: Introductionmentioning
confidence: 99%